Applying of the program codes for modeling the electron accelerator driven subcritical assembly - Ayzatskiy, M.I.; Dovbnya, A.M.; Khazhmuradov, M.A.; Prokhorets, I.M.; Prokhorets, S.I.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2005)
Some physical aspects of the electron accelerator driven subcritical nuclear assembly are considered. Results of calculations of some parameters of target and homogeneous subcritical assembly are presented.